2021
DOI: 10.7717/peerj.12316
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of factors affecting antibody response after administration of the BNT162b2 vaccine: a prospective study in Japan

Abstract: The aim of this study was to evaluate the antibody reaction after administration of the BNT162b2 vaccine, and to reveal the factors that affect antibody production. This prospective study was carried out in the Association of EISEIKAI Medical and Healthcare Corporation Minamitama Hospital, in Tokyo, Japan, from April 15, 2021 to June 09, 2021. All our hospital’s workers who were administered the BNT162b2 vaccine as part of a routine program were included in this study. We calculated the anti-SARS-CoV-2 spike-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…The most commonly reported conditions were hypertension, obesity, and asthma. There is some evidence that all three of these conditions can negatively affect immune responses to vaccination against other pathogens 40 44 as well as COVID-19 45 47 , where high-dose corticosteroid treatments used to treat severe asthma could also blunt vaccine responses 48 . At study entry, 8% of PLWH and 10% of controls were identified as COVID-19 convalescent based on the presence of anti-N antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported conditions were hypertension, obesity, and asthma. There is some evidence that all three of these conditions can negatively affect immune responses to vaccination against other pathogens 40 44 as well as COVID-19 45 47 , where high-dose corticosteroid treatments used to treat severe asthma could also blunt vaccine responses 48 . At study entry, 8% of PLWH and 10% of controls were identified as COVID-19 convalescent based on the presence of anti-N antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence regarding the association between BMI and vaccine‐induced antibody titers is limited and inconsistent ( 5 , 6 , 7 ). Given the sex difference in the distribution and function of adipocytes ( 8 ), the inconsistency among previous studies could be ascribed, at least in part, to the lack of consideration of sex.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding the association between BMI and vaccine-induced antibody titers is limited and inconsistent (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of eight (observational, case–control, and cross-sectional) studies reported a consistently lower antibody titer or seropositivity of COVID-19 vaccines that was associated with diabetes or poor diabetes control [ 9 ]. Subsequently, studies in Kuwait [ 10 ] and Japan [ 11 ] also reported lower concentrations of SARS-CoV-2 IgG spike antibody in patients with diabetes [ 10 , 11 ], whereas another Japanese study reported no significant association [ 12 ]. Most of these studies assessed diabetes based on participants’ self-report [ 9 , 10 , 12 ], which may miss undiagnosed diabetes.…”
Section: Introductionmentioning
confidence: 99%